GEOGRAPHIES OF PLACE ATTACHMENT: A PLACE-BASED MODEL OF MATERIALITY, PERFORMANCE, AND NARRATION. Issue 1 (1st January 2022) - Diener, Alexander C.; Hagen, Joshua
ABSTRACT: Attachments are intrinsic to the human condition. Geographers and related scholars are especially interested in place attachments and how they shape everyday routines (e.g. routes to work, shopping, social interactions), major life choices (e.g. places of residence, education, vacations), and identities (e.g. civic, national, religious). This article explores the complexity and richness of place attachment as researched across multiple disciplines while also outlining how geographers can make a more pronounced contribution. To that end, this article surveys place attachment research and in the process demonstrates the recent dearth of explicit research on the topic in geography compared to other disciplines, especially psychology. Subsequent sections show how geographers implicitly engage place attachment as a theme, even if by other names, and identify areas of possible synergy with cognate disciplinary approaches. In an effort to reinvigorate interest among geographers and emphasize the need for a multi-dimensional consideration of place as integral to understanding place attachment, this article provides a model of place attachment as an assemblage of materiality, performance, and narration. Rather than being static or deterministic, this model points to people's varied capacities to make and remake place attachments, and in doing so reasserts the power of place in place attachment.